Characterization and exopolysaccharide production of Bacillus velezensis DTA1 from Vietnamese atoll soil - Le, Thi Hue; Dinh, Hoang Tuan; Le, Mai Huong; Nguyen, Cong Tinh; Hoang, Quang Cuong (Brawijaya University, 2025)
Exopolysaccharides (EPS) and salt-tolerant, EPS-producing bacteria have attracted increasing attention due to their diverse applications across various fields. This study investigated the characteristics and EPS production potential of Bacillus velezensis DTA1, a salt-tolerant, EPS-producing strain isolated from coral island soil in Vietnam. Strain DTA1 demonstrated notable versatility in utilizing various carbon sources and exhibited a wide tolerance range to temperature, pH, and NaCl concentrations. Response Surface Methodology (RSM) was employed to optimize the culture conditions, resulting in an EPS yield of 32.80 g/L, achieved under optimized conditions of 7.26% sucrose, 3.27% NaCl, and pH 8.46. Through the evaluation of water-holding capacity, this study demonstrated the notable properties of the EPS and culture broth of strain DTA1 in enhancing water retention and soil component aggregation. These findings highlight the potential of strain DTA1 for arid land reclamation applications, particularly in harsh environments such as saline, alkaline, and arid coral sand areas on offshore islands.